70‐2: A Design for Near Eye Light Field Display. Issue 1 (28th June 2022) - Gao, Jian; Ma, Sen; Hong, Tao; Liang, Pengxia
Abstract : In this paper, a light field display system with the continuous imaging depths that can be focused by the monocular eye is proposed. Similar to viewing the real world, the different imaging depths can be viewed by the crystalline lens focusing without the visual fatigue.